Low-dielectric high-flame-retardant cable material as well as preparation method and application thereof
By using a variety of resins and flame retardants of a specific proportion in cable materials, the problems of large dielectric loss and insufficient flame retardant performance in high-frequency environments are solved, and cable materials with low dielectric constant, high flame retardant performance and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202411667143.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-11
AI Technical Summary
The existing cable materials have large dielectric loss in high-frequency environments and lack flame retardant performance, making it difficult to meet the needs of high-speed data transmission and security.
A specific proportion of polyolefin resins, fluorinated resins, cycloalkane oils, fluorinated PPOs, composite halogen-free flame retardants, antioxidants and dispersants are used to accurately control the content of each component, reduce the dielectric constant and dielectric loss, and at the same time improve the flame retardant performance.
It significantly reduces the dielectric constant and dielectric loss of cable materials, improves flame retardant performance and mechanical properties, and enhances the performance of cables under high temperature and high pressure conditions.
Smart Images

Figure CN119592003A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables and relates to a low-dielectric and highly flame-retardant cable material and a preparation method and application thereof. Background Art
[0002] As a core component of modern power transmission and communication systems, the importance of cables is self-evident. Cables have been widely used in various fields due to their excellent conductivity, stable transmission quality and flexible laying methods. In the power system, cables not only undertake the task of safely and efficiently transmitting the electricity generated by power plants to various power consumption points, but also are the key to ensuring the normal operation of industrial production and daily life. From home lighting to the operation of large industrial equipment, cables are everywhere. They are like the blood vessels of the city, connecting every corner that needs power support and ensuring the smooth progress of social and economic activities.
[0003] In the field of communications, cables, as a medium for information transmission, have achieved long-distance, large-capacity data transmission, greatly promoting the development of information technology. Whether it is traditional telephone communications or modern Internet services, cables are the basis for realizing these functions. In particular, with the popularization of new-generation communication technologies such as 5G, the demand for high-speed data transmission is increasing, and the quality and technical level of cables are directly related to the stability and efficiency of the communication system. In this context, the importance of high-frequency cables has become increasingly prominent. It not only plays an important role in academic research, but also occupies an indispensable position in industrial applications and daily life. The outstanding performance of high-frequency cables in high-speed data transmission and signal processing is due to their ability to respond quickly to changes in electric fields in their design, which requires cable materials to have low dielectric constants and dielectric losses to reduce signal delays, distortions or attenuation. Therefore, the research and development of new cable materials, especially those that can effectively reduce dielectric losses, has become one of the key directions for the development of the industry.
[0004] At the same time, as modern society's dependence on electricity and communications continues to deepen, the safety of cables has gradually become a focus of attention. Especially in high-density population areas and around important facilities, once a cable fire occurs, the consequences are disastrous. For this reason, flame-retardant cable materials came into being, and the fire resistance of cables is improved by adding specific flame retardants or other technical means to the cable materials. When a fire occurs, flame-retardant cable materials can effectively prevent the spread of fire, reduce the burning speed and intensity, and buy precious time for personnel evacuation and rescue. This type of cable also needs to significantly reduce the emission of toxic smoke and harmful gases, and reduce the impact of fire on human health and the natural environment. Therefore, the development and application of flame-retardant cable materials is not only a technological innovation to improve cable performance, but also an important measure to ensure public safety and social sustainable development. Summary of the invention
[0005] The purpose of the present invention is to provide a low-dielectric and highly flame-retardant cable material in view of the above-mentioned problems existing in the prior art, which has good mechanical properties and flame-retardant properties as well as a low dielectric constant.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A low-dielectric and highly flame-retardant cable material, comprising the following raw materials in parts by mass: 45-55 parts of oil-filled thermoplastic elastomer, 10-40 parts of fluorinated resin, 10-20 parts of fluorinated polyphenylene ether, 35-45 parts of polyolefin, 20-40 parts of composite halogen-free flame retardant, 0.5-2.0 parts of antioxidant, and 0.5-2.0 parts of dispersant.
[0008] In the above-mentioned low-dielectric and high-flame-retardant cable material, the oil-filled thermoplastic elastomer is prepared by adding cycloalkane oil to hydrogenated styrene-butadiene block copolymer and then heating it.
[0009] Preferably, the amount of cycloparaffin oil added is 10-30% of the mass of the hydrogenated styrene-butadiene block copolymer.
[0010] In the present invention, cycloalkane oil can, under the premise of not changing the basic chemical property of hydrogenated styrene-butadiene block copolymer (SEBS), by filling the space between its molecular chains, reduce the viscosity of material, make it easier to flow in the process, thereby be convenient to extrusion, injection molding and other molding operations, this not only improves the flexibility of production process, can also reduce equipment wear and tear, extend the service life.But when the addition of cycloalkane oil exceeds a certain limit, the physical and mechanical properties of SEBS will be negatively affected on the contrary, specifically manifested as the decline of material hardness, the weakening of tensile strength and the increase of permanent deformation.This is because excessive cycloalkane oil can weaken the interaction force between SEBS molecular chains, causes the material internal structure to become loose, thereby affects its overall mechanical property.In extreme cases, excessive softening may occur in material and even the problem of being unable to maintain shape, which constitutes a challenge to the practical application of cable material.
[0011] In the above-mentioned low-dielectric and high-flame-retardant cable material, the fluorinated resin has the following structural formula:
[0012]
[0013] Wherein (m+q):(n+p)=0.20-0.33:1, and m:q=0.2-0.4:1.
[0014] In the above-mentioned low-dielectric and high-flame-retardant cable material, the method for preparing the fluorinated resin specifically comprises the following steps:
[0015] S1, dissolving a hydrogenated styrene-butadiene block copolymer in an organic solvent, then adding 2-(trifluoromethyl)benzoyl chloride and anhydrous AlCl3, stirring, washing, heating and reacting to obtain a white solid;
[0016] S2, dissolving the white solid in an organic solvent, then adding trifluoroacetic acid and triethylsilane to carry out heating reaction, and extracting the organic layer after the reaction is completed;
[0017] S3, then precipitate, filter and dry to obtain the fluorinated resin.
[0018] Preferably, the organic solvent is dichloromethane.
[0019] Preferably, in step S1, the product is washed with methanol and then heated to obtain a white solid.
[0020] Preferably, the mass ratio of hydrogenated styrene-butadiene block copolymer, 2-(trifluoromethyl)benzoyl chloride and anhydrous AlCl3 is 1:(0.3-0.35):(0.2-0.25).
[0021] Preferably, the heating reaction temperature in step S1 is 55-65° C. and the reaction time is 20-28 h.
[0022] Preferably, the mass ratio of the white solid, trifluoroacetic acid and triethylsilane is 1:35-45:3.5-4.5.
[0023] Preferably, the heating reaction temperature in step S2 is 90-120° C. and the reaction time is 20-28 h.
[0024] Preferably, in step S2, an alkaline solution is used to extract the organic layer, and the alkaline solution is KOH.
[0025] Preferably, step S3 precipitation is to add methanol to precipitate solids.
[0026] In the present invention, the fluorine atoms in the fluorinated resin can significantly reduce the polar interactions between molecules due to their non-polar characteristics, thereby effectively reducing the dielectric constant of the material. This characteristic is particularly important for high-frequency cables, because in high-frequency environments, the reduction of the dielectric constant means the reduction of energy loss during signal transmission, thereby improving the transmission quality and efficiency of the signal. In addition, fluorine atoms can also produce a synergistic effect with flame-retardant elements such as phosphorus and nitrogen, further enhancing the flame retardant properties of the material, so that the cable can better prevent the spread of flames when encountering high temperatures or fire sources, and protect the safety of personnel and property. However, the amount of fluorinated resin added is not the higher the better. If the amount added is insufficient, the performance improvement effect brought about will not be obvious, and the advantages of the fluorinated resin cannot be fully utilized. On the contrary, if the amount added is too large, excessive fluorinated resin may cause a series of negative effects. First, too much fluorinated resin will increase the dielectric constant due to the enhancement of intermolecular interactions, which is contrary to the desired effect. Secondly, excessive fluorinated resin may cause the molecular structure to aggregate or phase separate, which will not only affect the uniformity of the material, but also increase the degree of electronic polarization and dipole polarization, thereby increasing dielectric loss and reducing the electrical properties of the material. In order to avoid the above problems while improving performance, the present invention controls the addition amount of fluorinated resin to between 10-40 parts. Within the range of 10-40 parts, the introduction of fluorinated resin can effectively reduce the polar interaction between molecules, significantly reduce the dielectric constant, and improve the efficiency and quality of signal transmission. Especially in high-frequency applications, this optimization effect is particularly obvious, which helps to improve the transmission bandwidth and reliability of the cable. Moreover, the synergistic effect of fluorine atoms and flame retardant elements such as phosphorus and nitrogen can be fully exerted within this addition amount range, significantly improving the flame retardant properties of the material, which means that the cable can better suppress the spread of flames when encountering a fire, reduce the generation of toxic smoke, and buy precious time for personnel evacuation and fire extinguishing; a reasonable addition amount of fluorinated resin can avoid the aggregation or phase separation of molecular structure, ensure the uniformity and consistency of the material, and at the same time, the addition amount within this range will not have a negative impact on the processing performance of the material, ensuring the good fluidity and processability of the cable material during the production process.
[0027] In the above-mentioned low-dielectric and high-flame-retardant cable material, the fluorinated polyphenylene ether has the following structural formula:
[0028] Where n=80-160.
[0029] The addition of fluorinated polyphenylene ether (F-PPO) in the present invention can significantly improve the dielectric properties and flame retardant properties of cable materials, and the non-polar properties of fluorine atoms reduce the polar interactions between molecules, effectively reduce dielectric constant and dielectric loss, and improve the efficiency and quality of signal transmission. At the same time, the introduction of fluorine atoms is combined with the carbonization of polyphenylene ether, which reduces the flammability of the material, and promotes the formation of a dense carbon layer during combustion, thereby enhancing the flame retardant properties of the material. However, the effect is not obvious when the addition amount is too little, and the addition amount is too much and may cause uneven dispersion, affecting the mechanical properties of the material and increasing dielectric loss. Therefore, the preferred fluorinated polyphenylene ether addition amount is 20-30 parts, to ensure the best balance of the material between dielectric properties and flame retardant properties.
[0030] In the above-mentioned low-dielectric and high-flame-retardant cable material, fluorinated polyphenylene ether (PPO) is obtained by modifying polyphenylene ether with 3,5-bis(trifluoromethyl)phenol.
[0031] Preferably, the modification process comprises the following steps:
[0032] S1. Dissolve PPO in toluene at 80-95°C under a nitrogen atmosphere, then add 3,5-bis(trifluoromethyl)phenol and stir evenly;
[0033] S2, then add toluene BPO solution dropwise to carry out high temperature reaction;
[0034] S3. After the reaction is completed, the fluorinated PPO is obtained by cooling, washing, filtering and finally vacuum drying.
[0035] Preferably, the amount of 3,5-bis(trifluoromethyl)phenol added is 45-55% of the mass of PPO.
[0036] Preferably, the amount of toluene BPO added is 5-15% of the mass of PPO.
[0037] Preferably, the vacuum drying temperature is 100-120°C and the time is 20-28h.
[0038] In the above-mentioned low-dielectric and highly flame-retardant cable material, the composite halogen-free flame retardant is a mixture of piperazine pyrophosphate, ammonium polyphosphate and melamine cyanurate in a mass ratio of 3:(2-4):(1-2).
[0039] In the above-mentioned low-dielectric and high-flame-retardant cable material, the polyolefin includes at least one of ethylene-butene copolymer, polyethylene and polypropylene.
[0040] In the above-mentioned low-dielectric and high-flame-retardant cable material, the antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 164, antioxidant DNP, and antioxidant TNP.
[0041] Preferably, the antioxidant is antioxidant 1010 and antioxidant 168 in a mass ratio of 1:(0.4-0.6).
[0042] In the above-mentioned low-dielectric and highly flame-retardant cable material, the dispersant is a stearic acid dispersant, specifically including at least one of stearic acid and stearate.
[0043] The present invention also provides a method for preparing the above-mentioned low-dielectric and high-flame-retardant cable material, the method comprising the following steps:
[0044] S1, prepare the above raw materials;
[0045] S2, mixing the oil-filled thermoplastic elastomer, the fluorinated resin and the fluorinated polyphenylene ether, and then performing a banburying treatment, and then crushing to obtain a fluorine-containing masterbatch;
[0046] S3, mixing polyolefin, composite halogen-free flame retardant, antioxidant and dispersant, and then extruding and granulating to obtain polyolefin masterbatch;
[0047] S4. Mix the fluorine-containing masterbatch and the polyolefin masterbatch, and then extrude and granulate to obtain a low-dielectric flame-retardant cable material.
[0048] The present invention also provides a highly flame-retardant cable with low dielectric constant and dielectric loss, characterized in that the highly flame-retardant cable is made from the above-mentioned cable material or the cable material prepared by the above-mentioned method.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] 1. The cable material of the present invention adopts polyolefin resin, fluorinated resin, cycloalkane oil, fluorinated PPO, composite halogen-free flame retardant, antioxidant and dispersant and other ingredients in specific proportions. By accurately controlling the content of each component, not only the dielectric constant and dielectric loss of the cable material are reduced, but also its flame retardant performance is greatly improved. In particular, the mixed use of hydrogenated styrene-butadiene block copolymer (SEBS) and polypropylene, as well as the filling of cycloalkane oil, effectively improves the processing performance and mechanical strength of the material.
[0051] 2. The present invention introduces benzene rings and trifluoromethyl groups in situ on SEBS and fluorinates PPO resin, thereby significantly increasing the distance between molecules inside the material, reducing the dielectric constant, and improving the heat resistance and chemical stability of the material. This modification strategy not only solves the problem of poor dielectric properties of traditional materials, but also enhances the performance of cable materials under harsh conditions such as high temperature and high pressure.
[0052] 3. The present invention uses a composite halogen-free flame retardant composed of piperazine pyrophosphate, ammonium polyphosphate, and melamine cyanurate. Compared with a single flame retardant, this composite solution can achieve excellent flame retardant effects at a lower addition amount while maintaining good mechanical properties. In addition, the carbonization of the PPO resin and the composite flame retardant system produce a good synergistic effect, further enhancing the flame retardant properties.
[0053] 4. The present invention proposes a preparation method of staged mixing and banburying granulation, namely, firstly adding cycloalkane oil into SEBS and performing heat drying treatment to obtain oil-extended SEBS; then kneading the oil-extended SEBS with raw materials such as fluorinated SEBS and fluorinated PPO and performing banburying granulation, and finally mixing with other components for extrusion molding. This method effectively solves the problem of uneven powder dispersion, ensures the uniform distribution of each component in the final product, and improves the overall performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 The PPO raw material and fluorinated PPO of Example 1; a. PPO raw material, b. fluorinated PPO;
[0055] Figure 2 SEBS masterbatch 1 before crushing after mixing treatment in Example 1 and Comparative Example 1; c. Example 1, d. Comparative Example 1;
[0056] Figure 3 The low dielectric and highly flame retardant cable material prepared in Example 1;
[0057] Figure 4 The SEM image and EDS-fluorine element image of the low-dielectric and high-flame-retardant cable material prepared in Example 1; e. SEM image, f. EDS-fluorine element image. DETAILED DESCRIPTION
[0058] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0059] Embodiment 1:
[0060] S1. Completely dissolve SEBS (4 g) of TSRC 6159 in dichloromethane (160 ml) at room temperature under N2 atmosphere, add 2-(trifluoromethyl)benzoyl chloride (1.37 g, 6.58 mmol) and anhydrous AlCl3 (0.88 g, 6.58 mmol), wherein 2-(trifluoromethyl)benzoyl chloride and AlCl3 are equimolar, and stir the mixture at room temperature for 4 hours, wash the reaction mixture several times with anhydrous methanol, and then continue at 60°C for 24 hours to obtain a white solid product.
[0061] S2. Dissolve the obtained white solid product in dichloromethane (100 ml) under N2 atmosphere, then add trifluoroacetic acid and triethylsilane, the mass ratio of white solid, trifluoroacetic acid and triethylsilane is 1:39.5:4.1, heat the mixture to 100°C for 24 hours, then cool the reaction product to room temperature, add it to KOH solution (0.5 mol / l, 50 ml), extract the organic layer, then add methanol to precipitate the solid, filter the solid and vacuum dry it at room temperature for 24 hours to obtain the product fluorinated SEBS;
[0062] Fluorinated SEBS has the structural formula shown below:
[0063]
[0064] In the structural formula of the fluorinated resin, (m+q):(n+p)=0.28:1, wherein the ratio of m to q is 0.3:1;
[0065] S3, 50g Figure 1 The PPO shown in -a was dissolved in 200 mL of 90°C toluene under nitrogen, and then 25 g of 3,5-bis(trifluoromethyl)phenol was added and stirred to dissolve evenly. 50 mL of toluene BPO solution (1 g / 10 mL) was added dropwise within 1.5 h, and then the reaction was maintained at 90°C for 3 h. The mixture was cooled to room temperature, and an excess of methanol was added to precipitate the product. After filtering the mixture, it was washed with a saturated NaHCO3 aqueous solution to remove the residual BPO. After vacuum drying at 110°C for 24 h, a yellow-white Figure 1 -b Fluorinated PPO shown;
[0066] Fluorinated PPO has the structural formula shown below:
[0067]
[0068] S4, adding 10%wt of cycloparaffin oil to the hydrogenated styrene-butadiene block copolymer, dispersing it evenly and then placing it in an oven at 90°C for 12h to obtain oil-filled SEBS;
[0069] S5, knead 10 parts of fluorinated SEBS, 10 parts of fluorinated PPO and 50 parts of oil-extended SEBS according to their mass fractions and then knead them to obtain Figure 2 The material shown in -c is crushed to obtain a fluorine-containing SEBS masterbatch 1;
[0070] The internal kneading process is to put the kneaded material into the internal mixer from the feeding port, and fall into the upper part of the two relatively rotating rotors. Under the pressure and friction of the top bolt, the material is brought into the gap between the two rotors and subjected to kneading. After the internal kneading is completed, the material is discharged from the internal mixer, cut into small pieces while hot, and then cooled to room temperature. The speed is set to 60r / min and the temperature is 210℃.
[0071] S6, adding 36 parts of composite halogen-free flame retardant, 1.5 parts of antioxidant, 2 parts of stearic acid and 40 parts of polypropylene into a high-speed mixer according to their weight proportions, mixing for 3 minutes, and extruding and granulating the obtained mixture to obtain polyolefin resin masterbatch II;
[0072] The composite halogen-free flame retardant is a mixture of piperazine pyrophosphate, ammonium polyphosphate and melamine cyanurate in a mass ratio of 3:4:2;
[0073] The antioxidants are antioxidant 1010 and antioxidant 168 in a mass ratio of 2:1;
[0074] Melamine cyanurate is MCA, CAS number is 37640-57-6;
[0075] S7. The fluorine-containing SEBS masterbatch 1 and the polyolefin resin masterbatch 2 are mixed, extruded into granules, and then injection molded to obtain a low-dielectric flame-retardant cable material.
[0076] The specific extrusion granulation process is to mix the fluorine-containing SEBS masterbatch 1 and the polyolefin resin masterbatch 2 and put them into the feed port, plasticize them through the pushing and shearing action of the screw, and then continuously pass through the die to form, draw the wire and cool it through water, and finally pass through the pelletizer to obtain Figure 3 The feed rate in the extruder is 40, and the speed of the main screw is 80. The temperature zones 1 to 10 of the twin-screw extruder during the extrusion granulation process are set as follows: 200°C, 205°C, 210°C, 215°C, 215°C, 215°C, 215°C, 210°C, 200°C, and 190°C.
[0077] Figure 4 The SEM image and EDS-fluorine element image of the low-dielectric and high-flame-retardant cable material prepared in Example 1; a. SEM image, b. EDS-fluorine element image. It can be seen from the figure that the fluorine element distribution of the low-dielectric and high-flame-retardant cable material prepared by the present invention is very uniform, which greatly improves the heat resistance and chemical stability of the cable material.
[0078] Embodiment 2:
[0079] S1. SEBS (4 g) of Yuehua YH-503T was completely dissolved in dichloromethane (160 ml) under N2 atmosphere at room temperature, 2-(trifluoromethyl)benzoyl chloride (1.37 g, 6.58 mmol) and anhydrous AlCl3 (0.88 g, 6.58 mmol) were added, wherein 2-(trifluoromethyl)benzoyl chloride and AlCl3 were equimolar, and the mixture was stirred at room temperature for 4 hours, the reaction mixture was washed several times with anhydrous methanol, and then continued at 60°C for 24 hours to obtain a white solid product.
[0080] S2. Dissolve the obtained white solid product in dichloromethane (100 ml) under N2 atmosphere, then add trifluoroacetic acid and triethylsilane, the mass ratio of white solid, trifluoroacetic acid and triethylsilane is 1:39.5:4.1, heat the mixture to 100°C for 24 hours, then cool the reaction product to room temperature, add it to KOH solution (0.5 mol / l, 50 ml), extract the organic layer, then add methanol to precipitate the solid, filter the solid and vacuum dry it at room temperature for 24 hours to obtain the product fluorinated SEBS;
[0081] Fluorinated SEBS has the structural formula shown below:
[0082]
[0083] In the structural formula of the fluorinated resin, (m+q):(n+p)=0.33:1, wherein the ratio of m to q is 0.4:1;
[0084] S3, 50g PPO was dissolved in 200mL of 90℃ toluene under nitrogen, and then 25g 3,5-bis(trifluoromethyl)phenol was added and stirred to dissolve evenly, 50mL toluene BPO solution (1g / 10mL) was added dropwise within 1.5h, and then the reaction was maintained at 90℃ for 3h, cooled to room temperature, and the product was precipitated by adding excess methanol. After filtering the mixture, it was washed with saturated NaHCO3 aqueous solution to remove residual BPO, and finally yellow-white fluorinated PPO was obtained after vacuum drying at 110℃ for 24h;
[0085] Fluorinated PPO has the structural formula shown below:
[0086]
[0087] S4, adding 10%wt of cycloparaffin oil to the hydrogenated styrene-butadiene block copolymer, dispersing it evenly and then placing it in an oven at 90°C for 12h to obtain oil-filled SEBS;
[0088] S5. According to the mass proportions, 10 parts of fluorinated SEBS, 10 parts of fluorinated PPO and 45 parts of oil-extended SEBS are kneaded and mixed, and the mixture is crushed to obtain a fluorinated SEBS masterbatch 1.
[0089] The process of internal mixing is to put the kneaded material into the internal mixer from the feeding port, and it falls into the upper part of the two relatively rotating rotors. Under the pressure and friction of the top bolt, it is brought into the gap between the two rotors and subjected to kneading. After the internal mixing is completed, the material is discharged from the internal mixer, cut into small pieces while hot, and then cooled to room temperature. The speed is set to 60r / min and the temperature is 210℃.
[0090] S6, adding 18 parts of composite halogen-free flame retardant, 0.5 parts of antioxidant, 0.5 parts of stearic acid and 35 parts of polypropylene into a high-speed mixer according to their weight proportions, mixing for 3 minutes, and extruding and granulating the obtained mixture to obtain polyolefin resin masterbatch II;
[0091] The composite halogen-free flame retardant is a mixture of piperazine pyrophosphate, ammonium polyphosphate and melamine cyanurate in a mass ratio of 3:4:2;
[0092] The antioxidants are antioxidant 1010 and antioxidant 168 in a mass ratio of 2:1;
[0093] S7. The fluorine-containing SEBS masterbatch 1 and the polyolefin resin masterbatch 2 are mixed, extruded into granules, and then injection molded to obtain a low-dielectric flame-retardant cable material.
[0094] The specific extrusion granulation process is to mix the fluorine-containing SEBS masterbatch 1 and the polyolefin resin masterbatch 2 and put them into the feed port, plasticize them through the pushing and shearing action of the screw, and then continuously pass through the die to form, draw the wire and cool it through water, and finally get the pellets through the pelletizer. The feeding speed in the extruder is 40, and the speed of the main screw is 80. The temperature zones 1 to 10 of the twin-screw extruder during the extrusion granulation process are set as follows: 200℃, 205℃, 210℃, 215℃, 215℃, 215℃, 215℃, 210℃, 200℃, 190℃.
[0095] Embodiment 3:
[0096] S1. Completely dissolve SEBS (4 g) of Kraton G1642 in dichloromethane (160 ml) under N2 atmosphere at room temperature, add 2-(trifluoromethyl)benzoyl chloride (1.37 g, 6.58 mmol) and anhydrous AlCl3 (0.88 g, 6.58 mmol), wherein 2-(trifluoromethyl)benzoyl chloride and AlCl3 are equimolar, and stir the mixture at room temperature for 4 hours, wash the reaction mixture several times with anhydrous methanol, and then continue at 60°C for 24 hours to obtain a white solid product.
[0097] S2. Dissolve the obtained white solid product in dichloromethane (100 ml) under N2 atmosphere, then add trifluoroacetic acid and triethylsilane, the mass ratio of white solid, trifluoroacetic acid and triethylsilane is 1:39.5:4.1, heat the mixture to 100°C for 24 hours, then cool the reaction product to room temperature, add it to KOH solution (0.5 mol / l, 50 ml), extract the organic layer, then add methanol to precipitate the solid, filter the solid and vacuum dry it at room temperature for 24 hours to obtain the product fluorinated SEBS;
[0098] Fluorinated SEBS has the structural formula shown below:
[0099]
[0100] In the structural formula of the fluorinated resin, (m+q):(n+p)=0.20:1, wherein the ratio of m to q is 0.2:1;
[0101] S3, 50g PPO was dissolved in 200mL of 90℃ toluene under nitrogen, and then 25g 3,5-bis(trifluoromethyl)phenol was added and stirred to dissolve evenly, 50mL toluene BPO solution (1g / 10mL) was added dropwise within 1.5h, and then the reaction was maintained at 90℃ for 3h, cooled to room temperature, and the product was precipitated by adding excess methanol. After filtering the mixture, it was washed with saturated NaHCO3 aqueous solution to remove residual BPO, and finally yellow-white fluorinated PPO was obtained after vacuum drying at 110℃ for 24h;
[0102] Fluorinated PPO has the structural formula shown below:
[0103]
[0104] S4, adding 10%wt of cycloparaffin oil to the hydrogenated styrene-butadiene block copolymer, dispersing it evenly and then placing it in an oven at 90°C for 12h to obtain oil-filled SEBS;
[0105] S5. According to the mass proportions, 40 parts of fluorinated SEBS, 20 parts of fluorinated PPO and 55 parts of oil-extended SEBS are kneaded and mixed, and the mixture is crushed to obtain a fluorinated SEBS masterbatch 1.
[0106] The process of internal mixing is to put the kneaded material into the internal mixer from the feeding port, and it falls into the upper part of the two relatively rotating rotors. Under the pressure and friction of the top bolt, it is brought into the gap between the two rotors and subjected to kneading. After the internal mixing is completed, the material is discharged from the internal mixer, cut into small pieces while hot, and then cooled to room temperature. The speed is set to 60r / min and the temperature is 210℃.
[0107] S6, adding 40 parts of composite halogen-free flame retardant, 2.0 parts of antioxidant, 2.0 parts of stearic acid and 45 parts of polypropylene into a high-speed mixer according to their weight proportions, mixing for 3 minutes, and extruding and granulating the obtained mixture to obtain polyolefin resin masterbatch II;
[0108] The composite halogen-free flame retardant is a mixture of piperazine pyrophosphate, ammonium polyphosphate and melamine cyanurate in a mass ratio of 3:4:2;
[0109] The antioxidants are antioxidant 1010 and antioxidant 168 in a mass ratio of 2:1;
[0110] S7. The fluorine-containing SEBS masterbatch 1 and the polyolefin resin masterbatch 2 are mixed, extruded into granules, and then injection molded to obtain a low-dielectric flame-retardant cable material.
[0111] The specific extrusion granulation process is to mix the fluorine-containing SEBS masterbatch 1 and the polyolefin resin masterbatch 2 and put them into the feed port, plasticize them through the pushing and shearing action of the screw, and then continuously pass through the die to form, draw the wire through water and cool it, and finally get the pellets through the pelletizer. The feeding speed in the extruder is 40, and the speed of the main screw is 80. The temperature zones 1 to 10 of the twin-screw extruder during the extrusion granulation process are set as follows: 200℃, 205℃, 210℃, 215℃, 215℃, 215℃, 215℃, 210℃, 200℃, 190℃.
[0112] Embodiment 4:
[0113] The only difference from Example 1 is that no banburying treatment is performed in step S5.
[0114] Embodiment 5:
[0115] The only difference from Example 1 is that 40 parts of fluorinated SEBS, 20 parts of fluorinated PPO, 55 parts of oil-extended SEBS, 40 parts of composite halogen-free flame retardant, 2.0 parts of antioxidant, 2.0 parts of stearic acid and 45 parts of polypropylene are directly mixed and then extruded and granulated.
[0116] Comparative Example 1:
[0117] The only difference from Example 1 is that no fluorinated SEBS is added to the raw materials in step S5. 10 parts by mass of fluorinated PPO and 50 parts of oil-extended SEBS are kneaded and mixed to obtain Figure 2 -d indicated materials.
[0118] Comparative Example 2:
[0119] The only difference from Example 1 is that no fluorinated PPO is added to the raw materials in step S5.
[0120] Comparative Example 3:
[0121] The only difference from Example 1 is that the PPO in the raw material of step S5 is not subjected to fluorination treatment.
[0122] Comparative Example 4:
[0123] The only difference from Example 1 is that no oil-extended SEBS is added to the raw materials in step S5.
[0124] Comparative Example 5:
[0125] The only difference from Example 1 is that the SEBS in the raw material of step S5 is not subjected to oil filling treatment.
[0126] Comparative Example 6:
[0127] The only difference from Example 1 is that no composite halogen-free flame retardant is added in step S6.
[0128] The cable materials prepared in the above-mentioned Examples 1-5 and Comparative Examples 1-6 were subjected to performance testing, and the dielectric properties were tested using an AS2855 dielectric tester at a frequency of 1 MHZ. The flame retardant properties, dielectric properties and mechanical properties are shown in Table 1 below.
[0129] Table 1: Performance test results of cable materials prepared in Examples 1-5 and Comparative Examples 1-6
[0130]
[0131] In summary, the cable material of the present invention adopts polyolefin resin, fluorinated resin, cycloalkane oil, fluorinated PPO, composite halogen-free flame retardant, antioxidant and dispersant and other ingredients in specific proportions. By accurately controlling the content of each component, not only the dielectric constant and dielectric loss of the cable material are reduced, but also its flame retardant properties are greatly improved. In particular, the mixed use of hydrogenated styrene-butadiene block copolymer (SEBS) and polypropylene, as well as the filling of cycloalkane oil, effectively improves the processing performance and mechanical strength of the material.
[0132] The parts of the embodiments herein that are not exhaustive of the midpoint values of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.
[0133] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.
[0134] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A low dielectric and highly flame retardant cable material, characterized in that: The cable material comprises the following raw materials in parts by weight: 45-55 parts of oil-filled thermoplastic elastomer, 10-40 parts of fluorinated resin, 10-20 parts of fluorinated polyphenylene ether, 35-45 parts of polyolefin, 18-40 parts of composite halogen-free flame retardant, 0.5-2.0 parts of antioxidant, and 0.5-2.0 parts of dispersant.
2. A low dielectric and highly flame retardant cable material according to claim 1, characterized in that: The oil-extended thermoplastic elastomer is prepared by adding cycloalkane oil to hydrogenated styrene-butadiene block copolymer and heating it.
3. The low dielectric and highly flame retardant cable material according to claim 1, characterized in that: Fluorinated resin has the structural formula shown below: Among them, (m+q):(n+p)=0.20-0.33:1, and m:q=0.2-0.4:
1.
4. A low dielectric and highly flame retardant cable material according to claim 1 or 3, characterized in that: The method for preparing the fluorinated resin specifically comprises the following steps: S1, dissolving a hydrogenated styrene-butadiene block copolymer in an organic solvent, then adding 2-(trifluoromethyl)benzoyl chloride and anhydrous AlCl3, stirring, washing, heating and reacting to obtain a white solid; S2, dissolving the white solid in an organic solvent, then adding trifluoroacetic acid and triethylsilane to carry out heating reaction, and extracting the organic layer after the reaction is completed; S3, then precipitate, filter and dry to obtain the fluorinated resin.
5. The low dielectric and highly flame retardant cable material according to claim 1, characterized in that: Fluorinated polyphenylene ether has the structural formula shown below: Where n=80-160.
6. A low dielectric and highly flame retardant cable material according to claim 1 or 5, characterized in that: Fluorinated polyphenylene ether is obtained by modifying polyphenylene ether with 3,5-bis(trifluoromethyl)phenol.
7. The low dielectric and highly flame retardant cable material according to claim 1, characterized in that: The composite halogen-free flame retardant is a mixture of piperazine pyrophosphate, ammonium polyphosphate and melamine cyanurate in a mass ratio of 3:(2-4):(1-2).
8. The low dielectric and highly flame retardant cable material according to claim 1, characterized in that: The polyolefin includes at least one of ethylene-butene copolymer, polyethylene, and polypropylene.
9. A method for preparing a low-dielectric and highly flame-retardant cable material as claimed in claim 1, characterized in that: The method comprises the following steps: S1. Prepare the raw materials according to claim 1; S2, mixing the oil-filled thermoplastic elastomer, the fluorinated resin and the fluorinated polyphenylene ether, and then performing a banburying treatment, and then crushing to obtain a fluorine-containing masterbatch; S3, mixing polyolefin, composite halogen-free flame retardant, antioxidant and dispersant, and then extruding and granulating to obtain polyolefin masterbatch; S4. Mix the fluorine-containing masterbatch and the polyolefin masterbatch, and then extrude and granulate to obtain a low-dielectric flame-retardant cable material.
10. A highly flame-retardant cable with low dielectric constant and dielectric loss, characterized in that: The highly flame-retardant cable is made from the cable material described in claim 1 or the cable material prepared by the method described in claim 9.